USE OF THE LEXICAL UNITS OF THE "AHL" IN THE WORKS OF ALISHER NAVOI IN THE FRAMEWORK OF SPEECH STYLES (Scientific journal of the Fergana State University, 2025)
The article analyzes the features of the use of lexical units with the “ahl” component in the works of Alisher Navoi within the framework of speech styles. The study studies the etymology, semantic content of the word “ahl” and its functional forms of use in various contexts - religious, moral, scientific-didactic and artistic texts. In particular, the role of such expressions as “ahl husn”, “ahl taqvo”, “ahl safo” and “ahl riya” in Navoi’s style, expressive-emotional and semantic analysis of these units is carried out. The results of the article, along with highlighting the artistic thinking of the great thinker and his mastery of using lexical-semantic means, also substantiate the relevance of studying stylistic layers in Uzbek linguistics.